Pedagogical Translation Use by Scientific Approach in Teaching English - Masitowarni Siregar (BIRCU, 2019)
This research was conducted to find out the way the English teachers used translation and the reasons the teachers used it in the instructional activity with scientific approach. The information were obtained from the English teachers in MAN Medan. Descriptive qualitative research design was utilized in answering the research’s problems. No treatment in this study. Following descriptive qualitative research this study provided description of a phenomenon that occurred naturally without any an experiment intervention or an artificially contrived treatment. Observation and interview were utilised as the techniques of collecting data. The finding indicated that there were three English teachers in teaching English used scientific approach in the process of using and correcting words, phrase or sentences messages, elaborating structure and classroom management. Furthermore, the reasons of pedagogical translation use were to help communication in the classroom, develop the students teacher relation and facilitate foreign langaage understanding.